Local and global bifurcation for periodic solutions of hamiltonian systems via comparison theory for the spectral flow - Janczewska, Joanna; Starostka, Maciej; Waterstraat, Nils (Topological Methods in Nonlinear Analysis, 2026)
We obtain local and global bifurcation for periodic solutions of Hamiltonian systems by using a new way to apply a comparison principle of the spectral flow that was originally introduced by Pejsachowicz in a joint work with the third author. A particular novelty is the study of global bifurcation, which to the best of our knowledge has not been done via the spectral flow.